IGF-II as a neuroprotective and neuroplastic factor in an oxidative damage model induced by glucocorticoids - Lara Fernández, Estrella; Valverde, Nadia; De Luque, Vanessa; Boraldi, Federica; Santín-Núñez, Luis Javier; Pavía-Molina, José; Martín-Montañez, Elisa; García-Fernández, María Inmaculada (My University, 2018)
IGF-II is a pleiotropic hormone widely distributed in the CNS, which triggers its functions by binding to IGF-IR, InsulinR and IGFII / M6P (IGF-IIR) receptors. Recently, it has been proposed that the effects of IGF-II, interacting with IGF-IIR, are relevant not only for metabolism, growth and development, but also for neurotransmitter release, memory consolidation and neuroprotection under neurodegenerative processes. The results of our research group prove that IGF-II exerts metabolic, antioxidant and neuroprotective effects in aging. In relation to glucocorticoids, it has been revealed that the exposure of neural cells to high levels or prolonged incubation periods, produce synaptic alteration, neurodegeneration and neuronal death. Mechanisms of glucocorticoiddamage are mediated by oxidative stress induced by an increase in ROS, mitochondrial damage, decrease in antioxidant defenses, lipid and protein membrane damage, etc. AIM: To study the antioxidant and neuroprotective effect of IGF-II in a model of oxidative damage induced by glucocorticoids in aging. Results:Incubation of cells with CORT triggers oxidative damage, consuming antioxidant status. This oxidative stress produces damage and mitochondrial redistribution inducing synaptic changes, as shown the decrease in synaptophysin and PSD95 levels together with a decrease in the uptake and release of FM1-43, which may result in neurodegeneration. Incubation with IGF-II reverses these deleterious effects. Conclusions: Treatment of cells with IGF-II recovers the damage produced by CORT, restoring synaptic function and decreasing neurodegeneration. These outcomes can be attributed to an antioxidant effect mediated by the interaction of IGF-II with its specific IGF-IIR, which in turn mediates recovery of the redox balance via inhibition of ROS production, improvement of mitochondrial membrane potential / distribution and / or regulation of synaptic proteins.
IGF-II como factor neuroprotector y neuroplástico en un modelo de daño oxidativo
Keywords: Fisiología; IGF2; IGF2R; Mitochondria; Neuroprotection; OxidativeStress; Synapse